Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm working a Laplace's equation $\Delta F=0$ for a cube in Cartesian coordinates $((0,0,0),(a,a,a))$ and after separation I have $$\frac{X''(x)}{X(x)} +\frac{Y''(y)}{Y(y)}+\frac{Z''(z)}{Z(z)} = 0\tag{1}$$

with boundary conditions

$$ x=0 \Rightarrow F=F_0$$ $$ x=a \Rightarrow F=-F_0$$ $$ y=0 \Rightarrow F=0$$ $$ y=a \Rightarrow F=0$$ $$ z=0 \Rightarrow F=0$$ $$ z=a \Rightarrow F=0$$

Thinking about my boundary condition, I figured I'd want the Y and Z terms in $(1)$ to be equal to negative constants $-k^2$ and $-\ell^2$ so I could get a $\sin{\pi y\over a}\sin{\pi z\over a}$ out of them, and the X term to equal a negative constant $-j^2$ as well whence I'd take a $F_0\cos{2\pi x\over a}$. Problem is, if they are all negative constants, they can't add up to zero as in $(1)$! What other options do I have here? I don't want to take a positive $-j^2$ because

share|cite|improve this question
up vote 4 down vote accepted

Scale the variable such that $x' = \pi x/a$, $y' = \pi y/a$, $z' = \pi z/a$ first, we the equation still holds $$ \frac{X''(x')}{X(x')} +\frac{Y''(y')}{Y(y')}+\frac{Z''(z')}{Z(z')} = 0 $$ and we can still get what you mentioned in your question: $$ \begin{cases} Y'' = -k^2 Y \\ Y(0) = Y(\pi) = 0 \end{cases}, \quad \begin{cases} Z'' = -l^2 Z \\ Z(0) = Z(\pi) = 0 \end{cases}. $$ Slightly abuse of notation, these two lead to $$ Y_k(y) = \sin(ky),\quad\text{and}\quad Z_l(z) = \sin(lz). $$ Now $X$ satisfies: $$ X'' = (k^2 + l^2)X, $$ hence let $m = \sqrt{k^2+l^2}$: $$ X = a_{kl} e^{mx} + b_{kl} e^{-mx}, $$ where the coefficient $a_{kl}, b_{kl}$ depend on $k$ and $l$.

When $x = 0$: $$ F\big|_{x=0} =F_0 = \sum_{l=1}^{\infty}\sum_{k=1}^{\infty} (a_{kl}+b_{kl}) \sin(ky)\sin(lz)\tag{1} $$ When $x=\pi$: $$ F\big|_{x=\pi} =-F_0 = \sum_{l=1}^{\infty}\sum_{k=1}^{\infty} (a_{kl} e^{m\pi} + b_{kl} e^{-m\pi}) \sin(ky)\sin(lz) \tag{2} $$ For $\{ \sin(ky)\sin(lz)\}_{k,l=1}^{\infty}$ are orthogonal pairwise, multiply (1) by $\sin(ky)\sin(lz)$ and integrate on $(0,\pi)$ for $y$ and $z$: $$ F_0 \int^{\pi}_0\int^{\pi}_0 \sin(ky)\sin(lz)\,dydz =\int^{\pi}_0\int^{\pi}_0 (a_{kl}+b_{kl}) \sin^2(ky)\sin^2(lz)\,dydz, \tag{$1'$} $$ The right side only have one term for $k' \neq k$ or $l' \neq l$ $$ \int^{\pi}_0\int^{\pi}_0 \sin(ky)\sin(lz) \sin(k'y)\sin(l'z) \,dydz= 0, $$ this is the orthogonality I mentioned above. Now $(1')$ gives: $$ F_0\frac{1-(-1)^k}{k}\frac{1-(-1)^l}{l} = (a_{kl}+b_{kl})\frac{\pi^2}{4}. $$ Doing the same thing for (2) yields: $$ -F_0\frac{1-(-1)^k}{k}\frac{1-(-1)^l}{l} = (a_{kl} e^{m\pi} + b_{kl} e^{-m\pi})\frac{\pi^2}{4}. $$ When $k$ and $l$ are both odd, we have: $$ a_{kl} = - \frac{16F_0 (e^{-m\pi}+1)}{\pi^2 kl(e^{m\pi} - e^{-m\pi})},\text{ and } b_{kl} = \frac{16F_0 (e^{m\pi}+1)}{\pi^2 kl(e^{m\pi} - e^{-m\pi})}, $$ When one of $k$ and $l$ is even, we have: $$ a_{kl} = b_{kl} = 0. $$

Now the final solution can be obtained just by scaling back by the factor of $\pi/a$, also setting $k = 2p-1$, $l = 2q-1$, for $p,q \in \mathbb{N}$: $$ F = \frac{16F_0}{\pi^2}\sum_{p=1}^\infty\sum_{q=1}^{\infty} X_{pq}(x)\sin\frac{(2p-1)\pi y}{a} \sin\frac{(2q-1)\pi z}{a} $$ where $$X_{pq}(x) = - \frac{\cosh\frac{m\pi}{2} e^{m(x-1/2)\pi/a}}{(2p-1)(2q-1)\sinh(m\pi)} +\frac{\cosh\frac{m\pi}{2}e^{-m(x-1/2)\pi/a}}{(2p-1)(2q-1)\sinh(m\pi)} $$ and $$ m =\sqrt{(2p-1)^2+(2q-1)^2}. $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.